Aplikasi Al-Barzanji Nahdlatul Wathan (NW) berbasis Android - Rasyid Hardi Wirasasmita; Muhammad Zamroni Uska; Usuluddin Usuluddin; Muslihun Muslihun (Infotek: Jurnal Informatika dan Teknologi, 2022)
Nahdhatul Wathan (NW) is an Islamic mass organization from West Nusa Tenggara, more specifically in East Lombok. One form of love and respect for the NW organization can be realized by reading the sholawat Al-barzanji NW. However, Al-Barzanji books are used mostly by photocopy so that the letters, lines and sentences are less clear. The purpose of this study is 1). generated android-based Al-Barzanji application, 2). know the application based on media experts and 3). Know the user's response to the Android-based Al-Barzanji application for NW organizations. This research uses the ADDIE model with stages of analysis, design, development, implementation and evaluation. The research stage is carried out until the implementation stage with limited-scale trials. Data collection techniques use questionnaires addressed to Media experts and 20 people in User Response. The data analysis technique used is quantitative descriptive. The result of this study is the Android-based Al-Barzanji NW app. Application test results by media experts received a score of 96% (very decent) and user response by 94% (very high category). So, it can be concluded that this application is worth implemented for citizens as one of the media that can be used in reading sholawat al-barzanji.